Role of Motivation in Learning English as a Second Language – A Case Study of Tamil Students of the University of Jaffna - Shanmugayogini, R. (M.Phil. in Linguistics, 2004)
The motivational role in learning ESL particularly in conflict areas where students are dejected due to various adverse factors such as the low socio economic and cultural statuses and consequently develop some kind of animosity toward learning, appears to be acutely vital. In order to induce their interest and make them acquire the necessary aptitude for learning, the language teacher is expected to possess competence in identifying students of idiosyncrasies and peculiarities in the process of language learning in a complex situation and also the capacity to eliminate any fear and anxiety that may cause mental obstacle in the tender minds of students on the very outset. The multifarious motivational theories put forward by prominent researchers were analyzed and their implication and the proper adoption of suitable theories that accord the context of Sri Lankan educational institutions were suggested. The hindrances students confront are highlighted, causes recognized and remedies proposed. With the view of fortifying the empirical status of the thesis, a special study has been conducted on the behavior, attitude and motivation of students in the Faculties of Management Studies and Commerce and Arts of the University of Jaffna in learning ESL. The findings of the study were subjected to thorough analysis and some truths were derived. Paradigms with regard to the application of motivational strategies too were included in the thesis to aid the teacher of ESL. Since language teaching involves psychological scrutiny of students, the research incorporates some motivational theories of psychological background and relevance between the application of such theories in the classroom and the positive outcome of teaching has been established